Kabul airport suicide bombing attack: Mass casualty management at the EMERGENCY NGO Hospital. Issue 4 (10th October 2022) - Spagnolello, Ornella; Esmati, Shekiba; Amiri, Abdul Fahim; Shahir, Mir Abdul Azim; Gatti, Sofia; Portella, Gina; Langer, Martin
Abstract : This paper illustrates the key principles for the management of Mass Casualties (MC) involving civilians victims applied at the EMERGENCY'NGO Kabul Hospital (Afghanistan). Abstract : BACKGROUND: Terrorist attacks with large numbers of civilian victims are not uncommon in war-torn countries, and present a unique challenge for health care facilities with limited resources. However, these events are largely underreported and little is known about how the mass casualty events (MCEs) are handled outside of a military setting. METHODS: This study is a retrospective analysis of the MCE which ensued the Kabul Airport suicide attack (August 26, 2021) at the Kabul EMERGENCY NGO Hospital (Afghanistan). RESULTS: Within 6 hours, 93 causalities presented at our hospital. Of them, 36 severe injured were admitted. Mean age was 30.8 years (SD, 10.1 years). The most common injury mechanism was shell fragments. The most common injury site was head (63%; 23/36), followed by limbs (55.5%; 20/36) and thoracoabdominal region (30.5%; 11/36). Combined injuries occurred in 38.9% of cases. Patients receiving surgery presented more combined injuries in comparison with patients receiving only medical treatment (47.1% vs. 31.6%). Thoracoabdomen (25.0% vs. 15.4%) and/or extremity injury (42.9% vs. 28.6%) were more prevalent in the surgical group. Thirty major surgical procedures were carried out on 17 patients in the 9 hours following the first arrival. The rate of intensive care unit/high dependency unit admission was 36.1% and the 30-day in-hospital mortality was 16.6% (6/36). All deaths were recorded in the first 24 hours, and none of them received surgery. CONCLUSION: A large number of wounded patients must be anticipated after suicide bombing attacks. The authors report the challenges faced and key aspects of their management of MCEs. LEVEL OF EVIDENCE: Prognostic/Epidemiological; Level IV. Abstract :